JEWREINOW W POWOJENNEJ POLSCE. (UWAGI O SPEKTAKLU TEATR ODWIECZNEJ WOJNY TEATRU WYBRZEŻE) - Gracla, Jadwiga (Acta Neophilologica, 2018)
The present artile dealt with the post-war production of the stage play Theatre of the Eternal War by Nikolai Evreinov. The author discussed the history of stage presentations of Jevrenov’s drama in Poland. Then she developed the topic referred to in the title of the play in focus. Theatre of the Eternal War was presented in the Wybrzeże Theatre in 1967. Skillful costruction of the scenography, which only apparently resembles a naturalistic one, made it possible to maintain the sense as well as the humour of the text, which is difficult when a stage production of an author’s plays is made many years after the works had been written. In case of the performance discussed in this paper the division theatre/reality, typical for Evreinov, was succesfully maintained.